Resilience in action : working with youth across cultures and contexts - Ungar, Michael, 1963-; Liebenberg, Linda (University of Toronto Press, 2008)
"Mental health specialists and researchers contend that the development of resilience in youth is facilitated at several levels. Relational, cultural, individual, and governmental factors all have a strong influence over the mental well being of young people. Resilience in Action looks at youth interventions with a view to fostering resilience in those living in adverse situations and conditions. In order to provide a practical approach to the issue, the essays in this volume explore the components of successful interventions, encouraging the transmission of effective practices from one community to another across borders. It is organized into four sections, each dealing with a different aspect of work with at-risk youth. The first section focuses on individual health and the ways in which intervention and therapy strengthen personal resources. The second section explores the dynamics of interventions in relation to specific contexts and localized relationships, emphasizing holistic approaches to youth work. A review of the cultural relevance of resilience follows in section three, and the fourth considers ways of increasing the accessibility to resources that encourage healthy development."--Pub. desc